Respiratory viruses in childhood asthma - Papadopoulos, N. G.; Kalobatsou, A. (Curr Opin Allergy Clin Immunol, 2007)
Several epidemiological studies have confirmed the association between viral respiratory infections and wheezing episodes or exacerbations of asthma in childhood. In contrast, whether particular viral infections can be protective or able to initiate asthma is still debated; recent studies reported herein have added to our understanding in several different domains, including natural history, virology and mechanisms.|Animal studies support the possibility that severe infections with respiratory syncytial virus early in life may be able to diverge the immune response towards an allergic phenotype; however, in human studies, predisposition seems dominating. Human rhinoviruses are increasingly being shown to be equally important as respiratory syncytial virus even in infancy. Newly discovered respiratory viruses have also been associated with asthma exacerbations. The interferon pathway is currently scrutinized with respect to virus-induced inflammation; furthermore, indications that viral infections may be associated with remodeling phenotypes have been recently published.|Notwithstanding the progress in epidemiology and pathogenesis of virus-induced asthma, more effort is needed in assessing possible strategies for treatment. Current treatments seem to be relatively ineffective, but new pathways give a hopeful message for future therapies.
Keywords: Asthma Child Humans Respiratory Tract Infections